EFEKTIVITAS EKSTRAK ETANOL BIJI MIMBA, MAHONI DAN SUREN TERHADAP LARVA Tenebrio molitor Linnaeus (Tenebrionidae: Coleoptera) - Wida Darwiati; Ujang Wawan Darmawan; Cheppy Syukur (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Neem, mahogany, and surian seeds contain secondary metabolites that can be used as biopesticides. This study aimed to determine the effectiveness of neem, mahogany, and surian seed extracts to the larvae of the Tenebrio molitor L. (Tenebrionidae: Coleoptera) at laboratory scale. The stages of the research were the preparation of seed extracts, phytochemical analysis of the extracts, and efficacy of extracts against T. molitor larvae. Dried seeds of neem, surian, and mahogany (water content < 10%) were ground (100 mesh) and macerated with 95% ethanol solvent for seven hours at 70 oC. The alkaloids, flavonoids, tannins, saponins, and steroids/the triterpenoid were then analyzed. The effectiveness of the extracts was testedagainst the 3rd larva of T. molinor. The experiment designed in Randomize block design, three replications, each with ten larvae. The first factor was seed extracts (neem, surian, and mahogany), while the second factor was five levels of extract concentration (0 mg;l-1, 9 mg.l-1, 15 mg.l-1, 30 mg.l-1 and 45 mg.l-1). Phytochemical analysis showed that mahogany seeds contained alkaloids and triterpenoids. Meanwhile, surian seeds contained tannin, alkaloid, steroid/triterpenoid, but neem seeds contained saponin and alkaloids. The mahogany, surian, and neem seed extracts were effective in causing significant mortality to T. molitor larvae. Ethanol extract of neem seeds was more toxic to larvae (LC50 = 0.72 mg.l-1), compared to mahogany (LC50 = 5.2 mg.l-1) and surian (LC50 = 7.02 mg.l-1). Mimba seed extract is more prospective to be developed as a botanical insecticide.